2005
DOI: 10.1038/sj.bjc.6602702
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neutrophil and monocyte counts in peripheral blood are associated with poor survival in patients with metastatic melanoma: a prognostic model

Abstract: We aimed to create a prognostic model in metastatic melanoma based on independent prognostic factors in 321 patients receiving interleukin-2 (IL-2)-based immunotherapy with a median follow-up time for patients currently alive of 52 months (range 15 -189 months). The patients were treated as part of several phase II protocols and the majority received treatment with intermediate dose subcutaneous IL-2 and interferon-a. Neutrophil and monocyte counts, lactate dehydrogenase (LDH), number of metastatic sites, loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
221
2
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(251 citation statements)
references
References 30 publications
19
221
2
9
Order By: Relevance
“…25 In patients with metastatic melanoma, elevated monocyte counts in peripheral blood were associated with poor survival. 26 In our study, we found a statistically significant association between a low L/ M ratio and CCS and DFS in STS patients in univariate as well as multivariate analysis for both data sets. These findings are in line with previously published studies from hematological cancer.…”
Section: Discussionsupporting
confidence: 60%
“…25 In patients with metastatic melanoma, elevated monocyte counts in peripheral blood were associated with poor survival. 26 In our study, we found a statistically significant association between a low L/ M ratio and CCS and DFS in STS patients in univariate as well as multivariate analysis for both data sets. These findings are in line with previously published studies from hematological cancer.…”
Section: Discussionsupporting
confidence: 60%
“…The prognostic value of the circulating neutrophil count has been reported previously in numerous malignancies, 21,22,26,41 including primary CRC. 23,39 Whilst it is possible that increasing neutrophil count is simply an epiphenomenon of the inflammatory response in the vicinity of the tumour, the emerging theory of 'immune enhancement' suggests that cells of the myeloid lineage, particularly neutrophils, are recruited from the circulation and play a direct role in promoting aggressive tumour phenotypes.…”
Section: Discussionmentioning
confidence: 66%
“…As reported previously, 20,22,26,41 a simple prognostic score for overall survival was derived from variables maintaining significance on multivariable analysis.…”
Section: Prognostic Scorementioning
confidence: 99%
“…Furthermore, we have previously reported an association between pretreatment elevated neutrophil counts in blood and poor prognosis in metastatic renal cell carcinoma and metastatic melanoma. [29][30][31] In the present study, we unfortunately had no full blood count from the patient population. Plasmacytoid dendritic cells (CD123þ) are known to be an important resource of interferons (IFNs) in their activated state.…”
Section: Discussionmentioning
confidence: 87%